PENGARUH BAURAN PROMOSI TERHADAP KEPERCAYAAN MEREK OLEH KONSUMEN PADA PRODUK KOSMETIK ORIFLAME DI KOTA LHOKSEUMAWE - Teuku Edyansyah (Departemen Manajemen, Universitas Syiah Kuala, 2018)
This study aimed to determine the effect of the promotion mix consists of advertising, sales promotion, public relations, personal selling, direct marketing and word of mouth on brand trust on Oriflame Cosmetics products in Lhokseumawe. And to determine the variables of the promotional mix of the most dominant influence on brand trust on Oriflame Cosmetics products in Lhokseumawe. Population of the study include the women who buy and wear cosmetics brand Oriflame products in Lhokseumawe. Samples taken in the amount of 100 respondents and the sampling technique used was accidental sampling technique. Data obtained from the questionnaires were then processed and analyzed by using multiple regression analysis. This analysis includes the validity and reliability, the classic assumption test, multiple linear regression analysis, hypothesis testing ttestand Ftest, and analysis of the coefficient of determination (Adjusted R2). Hypothesis testing using ttestshowed that the independent variables studied was shown to significantly affect the dependent variable brand trust. Then through the Ftestcan be seen that the advertising variable (X1), sales promotion (X2), public relations (X3), personal selling (X4), direct marketing (X5) and word of mouth (X6) simultaneously affect the dependent variable (brand trust) with a value of Fcount(51.914) Ftable(2,20). Adjusted R2, obtained at 0.755. This means that 75.5% confidence can be explained by the variable brand advertising, sales promotion, public relations, personal selling, direct marketing and word of mouth. While the remaining 24.5% of brand trust variables influenced by other factors outside of our model. Key Words Advertising, Sales Promotion, Public Relations, Personal Selling, Direct Marketing, Word Of Mouth, Brand Trust.